Pengaruh Strategi Diferensiasi Produk Kuliner Terhadap Peningkatan Daya Tarik Pelanggan Di Pasar Tradisional Bagan Batu: Strategi diferensiasi, keunikan produk, kualitas produk, inovasi rasa, daya tarik pelanggan - Hafizd Shaputra; Irwansyah Hasibuan (BJRM (Bongaya Journal of Research in Management), 2026)
This study aims to analyze the influence of culinary product differentiation strategies — encompassing product uniqueness, product quality, and flavor innovation — on customer attraction at Bagan Batu Traditional Market. A quantitative method was employed with 250 respondents selected through purposive sampling, analyzed using multiple linear regression with SPSS version 26. The t-test results indicate that product uniqueness (t = 2.971), product quality (t = 4.677), and flavor innovation (t = 6.551) each have a significant effect with significance values of 0.000–0.003. Simultaneously, the F-test yielded a value of 324.920 with a significance of 0.000, confirming that all three variables jointly have a positive and significant effect on customer attraction. Flavor innovation was identified as the most dominant variable. The coefficient of determination of 0.798 indicates that 79.8% of the variation in customer attraction is explained by the three variables, while the correlation value of 0.894 reflects a very strong relationship between product differentiation strategies and customer attraction. These findings imply that culinary vendors in traditional markets need to continuously optimize their product differentiation strategies to enhance customer attraction